Radiocesium migration in the litter layer of different forest types in Fukushima, Japan. (July 2018) - Kurihara, Momo; Onda, Yuichi; Kato, Hiroaki; Loffredo, Nicolas; Yasutaka, Tetsuo; Coppin, Frederic
Abstract: Cesium-137 ( 137 Cs) migration in the litter layer consists of various processes, such as input via throughfall, output via litter decomposition, and input from deeper layers via soil organism activity. We conducted litter bag experiments over 2 years (December 2014–November 2016) to quantify the inputs and outputs of 137 Cs in the litter layer in a Japanese cedar plantation ( Cryptomeria japonica ) and a mixed broadleaf forest dominated by Quercus serrata located 40 km northwest of the Fukushima Dai-ichi Nuclear Power Plant. The experiments included four conditions, combining contaminated and non-contaminated litter and deeper layer material, and the inputs and outputs were estimated from the combination of 137 Cs increases and decreases in the litter layer under each condition. The 137 Cs dynamics differed between the two forests. In the C. japonica forest, some 137 Cs input via throughfall remained in the litter layer, and downward 137 Cs flux passed through the litter layer was 0.42 (/year).Upward flux of 137 Cs from the deeper layer was very restricted, < 0.017 (/year). In the broadleaf forest, migration of 137 Cs in throughfall into deeper layers was restricted, downward 137 Cs flux was less than 0.003 (/year).Upward input of 137 Cs from the deeper layer was prominent, 0.037 (/year). 137 Cs output via litter decomposition was observed in both forests. The flux in the C. japonica forest was slower than that in the broadleaf forest, 0.12 and 0.15 (/year), respectively. Highlights: Cs fluxes in the litter layer were examined using litter bags in two forests. Downward and upward fluxes were considered separately in cedar and broadleaf sites. Cs migration was driven by litter decomposition in both forests. In the broadleaf site, upward flux from the deeper layer was observed. In the cedar forest, upward flux of Cs was restricted.